Optimization in the natural sciences : 30th Euro Mini-Conference, EmC-ONS 2014, Aveiro, Portugal, February 5-9, 2014. Revised selected papers /: 30th Euro Mini-Conference, EmC-ONS 2014, Aveiro, Portugal, February 5-9, 2014. Revised selected papers. (2015) - Unknown
No abstract available